Strategies of Islamic Religious Education Supervisors in Enhancing Madrasah Principals' and Teachers' Professionalism: A Case Study - Ahmad Mujaddid Syaikhul Islam; Wiwik Dyah Aryani (Jurnal Iman dan Spiritualitas, 2026)
This research is motivated by the critical role of Islamic religious education supervisors in enhancing the professionalism of madrasah principals and teachers, particularly at Madrasah Ibtidaiyah Yapida Sliyeg-Indramayu, given that educational quality is significantly influenced by the performance of teaching staff and school management. The purpose of this study is to analyze the strategies of Islamic religious education supervisors in their efforts to improve the professionalism of madrasah principals and teachers in this environment. This research used a case study method with a qualitative approach, involving observation, interviews, and documentation to obtain in-depth data on the implementation of supervision and coaching by supervisors. The results indicate that supervisory strategies, including instructional supervision, classroom visits, and administrative and managerial coaching, significantly improved the pedagogical, professional, and social competencies of teachers and madrasah principals. The conclusion of this study is that the active role of Islamic religious education supervisors is highly influential in improving the professionalism and quality of education in madrasahs, although several obstacles remain, including limited resources and a suboptimal understanding of the curriculum. These findings emphasise the need to strengthen supervisor capacity and foster closer collaboration between supervisors, madrasah principals, and teachers to achieve the goals of quality and religious education.